Impacts of hesperidin on whey protein functionality: Interacting mechanism, antioxidant capacity, and emulsion stabilizing effects - Wang, Yin; Guo, Yangkai; Zhang, Longtao; Yuan, Meilan; Zhao, Li; Bai, Chunqing; McClements, David Julian (Frontiers in Nutrition, 2023)
The objective of this work was to explore the possibility of improving the antioxidant capacity and application of whey protein (WP) through non-covalent interactions with hesperidin (HES), a citrus polyphenol with nutraceutical activity. The interaction mechanism was elucidated using several spectroscopic methods and molecular docking analysis. The antioxidant capacity of the WP-HES complexes was analyzed and compared to that of the proteins alone. Moreover, the resistance of oil-in-water emulsions formulated using the WP-HES complexes as antioxidant emulsifiers to changes in environmental conditions (pH, ion strength, and oxidant) was evaluated. Our results showed that HES was incorporated into a single hydrophobic cavity in the WP molecule, where it was mainly held by hydrophobic attractive forces. As a result, the microenvironments of the non-polar tyrosine and tryptophan residues in the protein molecules were altered after complexation. Moreover, the α-helix and β-sheet regions in the protein decreased after complexation, while the β-turn and random regions increased. The antioxidant capacity of the WP-HES complexes was greater than that of the proteins alone. Non-radiative energy transfer from WP to HES was detected during complex formation. Compared to WP alone, the WP-HES complexes produced emulsions with smaller mean droplet diameters, exhibited higher pH and salt stability, and had better oxidative stability. The magnitude of these effects increased as the HES concentration was increased. This research would supply valuable information on the nature of the interactions between WP and HES. Moreover, it may lead to the creation of dual-function antioxidant emulsifiers for application in emulsified food products.